2014
DOI: 10.1007/s00432-014-1690-7
|View full text |Cite
|
Sign up to set email alerts
|

miR-129-3p, as a diagnostic and prognostic biomarker for renal cell carcinoma, attenuates cell migration and invasion via downregulating multiple metastasis-related genes

Abstract: miR-129-3p may act as a promising diagnostic biomarker for discriminating ccRCC from benign tumors and normal tissues and an independent prognostic biomarker in ccRCC. miR-129-3p may exert its anti-metastatic function through modulating multiple targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 41 publications
1
56
0
Order By: Relevance
“…MiR-129-2 had a higher methylation ratio, indicating its potential as a methylation biomarker in early diagnosis of ESCC [7]. Considering that miR-129-3p was markedly decreased in ccRCC, it may act as a promising diagnostic biomarker for distinguishing ccRCC from benign tumors and normal tissues and an independent prognostic biomarker in ccRCC [29]. As shown in a recent study, the detection of gastric juice miR-129-1-3p and miR-129-2-3p may be an innovative choice for the diagnosis of gastric cancer [28].…”
Section: Mir-129 As a Biomarker For Cancer Diagnosis And Prognosismentioning
confidence: 99%
See 1 more Smart Citation
“…MiR-129-2 had a higher methylation ratio, indicating its potential as a methylation biomarker in early diagnosis of ESCC [7]. Considering that miR-129-3p was markedly decreased in ccRCC, it may act as a promising diagnostic biomarker for distinguishing ccRCC from benign tumors and normal tissues and an independent prognostic biomarker in ccRCC [29]. As shown in a recent study, the detection of gastric juice miR-129-1-3p and miR-129-2-3p may be an innovative choice for the diagnosis of gastric cancer [28].…”
Section: Mir-129 As a Biomarker For Cancer Diagnosis And Prognosismentioning
confidence: 99%
“…Ectopic expression of miR-129-3p robustly impaired RCC cell invasive and migratory properties. MiR-129-3p exerted its anti-metastatic function through modulating multiple metastasis-related genes, including SOX4, phosphorylation of focal adhesion kinase and MMP-2/9 expression [29]. MMP9 was also proved a target gene of miR-129 to govern metastasis in NSCLC cells [79].…”
Section: Mir-129 and Metastasismentioning
confidence: 99%
“…Growing evidence showed that miRNAs could act as novel biomarkers or therapy agent for various cancers, inculding RCC (17). For instance, the expression of was miR-129-3p significantly decreased in RCC, as a molecular diagnostic marker to distinguish RCC from benign tumors and normal tissues and a potential prognostic marker for RCC (18). Chen et al showed that miR-141 serves as a potential biomarker for discriminating RCC from normal tissues and a crucial suppressor of RCC cell proliferation and metastasis by modulating the EphA2/p-FAK/p-AKT/MMPs signaling cascade (19).…”
Section: Discussionmentioning
confidence: 99%
“…Su et al revealed that let-7d may suppress RCC growth, metastasis and tumor macrophage infiltration by targeting COL3A1 and chemokine ligand-7 (22). A study by Chen et al demonstrated that miRNA-129-3p attenuates cell migration and invasion of RCC by downregulating multiple metastasis-associated genes, and may also act as a diagnostic and prognostic biomarker for RCC (23). Wu et al revealed that miRNA-133b was downregulated in RCC cell lines and inhibited cell proliferation, migration and invasion of RCC cells (24).…”
Section: Introductionmentioning
confidence: 99%